DURABILITY OF NEWEST ALLOYS OF THE LEADING PRODUCERS OF HETEROGENEITY ARTICLES IN CONDITIONS OF IMPROVEMENT AND DEVELOPMENT OF WIRE DRAWING TECHNOLOGY AT RUP «BMZ» - D. G. Sachava; I. P. Lazebnikova (Литьë и металлургия)
It is shown that for increase of  fracture strength and wear resistance of  die blocks it is necessary to implement new types of  hard alloy with increased crack growth- and wear resistance.